Production Process of Burned Meatballs in Malang City: Overview of Multiculturalistic Aspects - Agnes Rebeca Ogos; Paskalia Valentine Risakota; Fransiskus Samuel (International Research & Development for Human Beings (IRDH), 2024)
Meatballs are foods that are in great demand by many people, which are made from processed beef. Now the menu of processed meatballs is varied, one of which is grilled meatballs. The purpose of this study is to find out what ingredients are used in the production process of grilled meatballs, what tools and machines are used for the production process of grilled meatballs, to know a review of multiculturalistic aspects such as what is needed in the production process of grilled meatballs, and also to find out what Quality control is used and used in the meatball production process in the city of Malang. The research method uses qualitative methods with Literature comparison analysis tools (literature comparisons) by taking as many as 2 respondents. The Production Process of Bakso Bakar in Malang City still uses manual and simple tools, as well as the attraction that makes customers from within the city and outside the city interested in buying Grilled Meatballs because of the unique way of burning it and the taste is good and tasty at a fairly cheap price, guaranteed quality and a strategic shop location for consumers to visit.